Democracy and neoliberalism : on the crisis of democratic legitimacy caused by neoliberal transformation. - Esposito, Marianna (Soft Power, 2014)
Time has run out for democratic sovereignty in the now bygone era of neoliberal governmentality and the time "bought" in the thirty year period after the Second World War with social Welfare State policies is the price we now have to pay in terms of public debt and distributional conflict in an irreversible crisis of representative democracy